Elevated Expression of STAT6, ERG, and miR-647 Expression as Predictive Biomarkers for Prostate Cancer - Yuan HZ; Jin SM; Yang WD; Du M; Wang L; Xiao L (International Journal of General Medicine)
Hua-Zun Yuan,1,* Sheng-Ming Jin,2,3,* Wen-Dong Yang,4,* Min Du,1 Lei Wang,1 Li Xiao1 1Department of Pathology, Huadong Hospital, Fudan University, Shanghai, People’s Republic of China; 2Department of Urology, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China; 3Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, People’s Republic of China; 4Cancer Institute, Xuzhou Medical University, Xuzhou, Jiangsu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Xiao, Department of Pathology, Huadong Hospital, Fudan University, No. 221 West Yan’an Road, Shanghai, People’s Republic of China, Tel +86-18916615822, Email fangjx0207@foxmail.comAim: The aim of this study was to investigate the clinical significance of STAT6, ERG, miR-647 in prostate cancer (PCa).Methods: This was a retrospective study. There were 210 consecutive patients diagnosed with prostate cancer or benign prostatic hyperplasia in our hospital from July 2020 to July 2023. Among those patients, 108 patients pathologically diagnosed as prostate cancer were divided into the prostate cancer group (PCa group), and 102 patients pathologically diagnosed as having benign prostatic hyperplasia were divided into the benign prostatic hyperplasia group (BPH group).Results: The levels of STAT6 mRNA, ERG mRNA, and miR-647 expression in prostate cancer tissue were higher than those in BPH tissues, with statistically significant differences (P< 0.05) . The levels of STAT6 mRNA, ERG mRNA, and miR-647 indicators in prostate cancer patients were not significantly different with respect to patient age and tumor size (P > 0.05) but were related to lymph node metastasis, T stage, and Gleason score (P < 0.05). On the other hand, the tPSA/fPSA had significantly different between two groups (P < 0.05). PCa group had smaller MRI sagittal diameter and anteroposterior diameter in comparison to BPH group (P < 0.05), furthermore, PCa group had larger PI-RAD in comparison to BPH group (P < 0.05).Conclusion: The higher level of STAT6, ERG, and miR-647 in prostate tissue are closely related to the occurrence of prostate cancer and have certain value in predicting the onset of prostate cancer.Keywords: prostate cancer, signal transducer and activator of transcription 6, ETS-related gene, miR-647, Prostate cancer